2006
DOI: 10.1016/j.anbehav.2005.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Stability and group specificity of stereotyped whistles in resident killer whales, Orcinus orca, off British Columbia

Abstract: Resident killer whales off British Columbia form four acoustically distinct clans, each with a unique dialect of discrete pulsed calls. Three clans belong to the northern and one to the southern community. Resident killer whales also produce tonal whistles, which play an important role in close-range communication within the northern community. However, there has been no comparative analysis of repertoires of whistles across clans. We investigated the structural characteristics, stability and group specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 50 publications
4
80
2
Order By: Relevance
“…Although no definitive study has been conducted demonstrating vocal learning in killer whales, several separate observations support both this conclusion (Bowles et al, 1988;Foote et al, 2006;Nousek et al, 2006;Riesch et al, 2006) and that cultural transmission may be the mechanism underlying development and acquisition of the vocal repertoire. Ford (1991) suggested that when pods become too large to afford all members adequate access to resources, they splinter into two or more smaller pods and acoustic dialects begin to diverge slowly through cultural drift whereby changes arise from small copying errors in vocal imitation and transmission.…”
Section: Killer Whales As Candidates For Using Culturementioning
confidence: 77%
“…Although no definitive study has been conducted demonstrating vocal learning in killer whales, several separate observations support both this conclusion (Bowles et al, 1988;Foote et al, 2006;Nousek et al, 2006;Riesch et al, 2006) and that cultural transmission may be the mechanism underlying development and acquisition of the vocal repertoire. Ford (1991) suggested that when pods become too large to afford all members adequate access to resources, they splinter into two or more smaller pods and acoustic dialects begin to diverge slowly through cultural drift whereby changes arise from small copying errors in vocal imitation and transmission.…”
Section: Killer Whales As Candidates For Using Culturementioning
confidence: 77%
“…In many taxa, acoustic signals encode social information about the sender, such as sex [2], age [3], size [4], reproductive status [5], group affiliation [6], or individual identity [7]. However, it is often unclear whether social information encoded in vocal signatures is voluntarily or involuntarily shared with conspecifics [1], and whether shared information is actually used by receivers [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Such acoustic 65 signals have been defined as private and they are usually rather quiet, comparatively high 66 in frequency, and highly modulated in order to be more prone to attenuation andsuch ultrasonic whistles did not occur in recordings of North Pacific residents or 114 transients. Although the vast majority of resident whistles seem to be variable in nature, 115 several stereotyped whistle types have been described that are often emitted in complex 116 sequences (Riesch et al 2006(Riesch et al , 2008. Compared to pulsed calls, killer whale whistles 117…”
mentioning
confidence: 99%
“…A priori probabilities were calculated based 242 on group-sizes, and these were then used to calculate the proportional-by-chance 243 accuracy by summing the squares of all prior probabilities. An overall classification 244 success for the model was provided, and the grouping variable was stereotyped whistle 245 category ('TW1', 'TW2', or 'TW3').resident killer whales from a previous study (Riesch et al 2006), and tested for 248 differences between stereotyped whistles of different killer whale populations by means 249 of a full-factorial multivariate GLM (MANOVA). The dependent variables were again z-250 transformed whistle parameters, and population ('transient', 'northern resident' or 251 'southern resident') was the fixed factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation